Effects of construal level and need for cognition on consumers' responses to temporally framed benefits - Youn, Seounmi; Kim, Hyuksoo (Journal of consumer behaviour, 2019)
Applying construal level (CL) theory as a theoretical framework, this study examined the conditions under which temporally framed messages are effective. A 2(temporal framing: near‐future vs. distant‐future rewards) × 2(CL: high vs. low) × 2(need for cognition: high vs. low) between‐subjects design was employed. Data from two online experiments showed that consumers generated more favorable responses to the ad when the temporal distance matched consumer CL. Low‐construal consumers, either chronic or primed, were found to prefer product information framed with near‐future rewards. This CL temporal match effect appeared for consumers high in need for cognition only. Further, the matched message enhanced consumers' perception of message quality and this perceived message quality mediated the effect of the CL temporal match on consumer responses to the ad. Theoretical and managerial implications were discussed.